2019
DOI: 10.5812/ijem.88343
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the International Association of Diabetes in Pregnancy Study Group Criteria with the Old American Diabetes Association Criteria for Diagnosis of Gestational Diabetes Mellitus

Abstract: ObjectivesThis study aimed to assess the prevalence of gestational diabetes mellitus (GDM) based on two sets of criteria, namely the old criteria suggested in 2009 by the American Diabetes Association and new criteria of the International Association of Diabetes in Pregnancy Study Group. We also evaluated the predictive power of the risk factors of GDM.MethodsPregnant women from three outpatient clinics in Tehran, Iran, participated in this cross-sectional observational study. During the first perinatal visit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In this study, a total of 118 healthy controls, 57 NDR cases, 64 NPDR cases and 61 PDR cases were enrolled. The diagnosis of type 2 DM was made according to the American Diabetes Association (ADA 2019) criteria[ 12 ]. The diagnosis and classification of DR cases were conducted based on retinal photographs according to were taken and graded according to the Diabetic Retinopathy preferred practice pattern (PPP)-updated 2019 guideline.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a total of 118 healthy controls, 57 NDR cases, 64 NPDR cases and 61 PDR cases were enrolled. The diagnosis of type 2 DM was made according to the American Diabetes Association (ADA 2019) criteria[ 12 ]. The diagnosis and classification of DR cases were conducted based on retinal photographs according to were taken and graded according to the Diabetic Retinopathy preferred practice pattern (PPP)-updated 2019 guideline.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, various studies investigated the possible risk factors associated with incidence of GDM. GDM was significantly higher in pregnant women with older age, poorer glycemic control, and higher BMI, which may be due to the reduction of insulin sensitivity in those women [1,4,6,8]. Most of the studies assessed the diagnostic accuracy of lowest FPG level in diagnosing GDM and only few studies assessed the diagnostic accuracy of lowest FPG level in ruling out GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM), defined as diabetes diagnosed during pregnancy in women without overt diabetes mellitus (DM), is one of the most important and common metabolic disorders during pregnancy [1]. GDM had wide range growing prevalence in different studies from 7.9 to 24.9% [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the increasing prevalence of overweight and obesity in recent years has been associated with the increasing prevalence of GDM, based on the IADPSG criteria, which exceeds all previous records. In this regard, two recent Iranian studies from Isfahan ( 9 ) and Tehran ( 10 ) reported the higher prevalence of GDM based on the IADPSG criteria (15.6% and 9.3%, respectively) than based on the old two-step criteria (7.1% and 4.2%, respectively). Moreover, two recent meta-analyses, one including nine observational studies and one including four clinical trials, showed adverse pregnancy and prenatal outcomes in GDM patients diagnosed by either method.…”
Section: Contextmentioning
confidence: 94%